EFEKTIVITAS KEBIJAKAN MAKROPRUDENSIAL BANK INDONESIA - Novrianti Putri Ardely; Syofriza Syofyan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
This thesis discusses the effectiveness of macroprudential policies Indonesia Bank in the control of property loans. The independent variables are dummy variables of the loan to value, interest rates on consumer loans, gross domestic product, and the interaction variables of loan to value with interest rates on consumer credit and the dependent variable is the property loans. The method used in this thesis is panel data regression method. This study aims to determine whether macroprudential policy instrument (loan to value) is effective to be applied in Indonesia. The results showed that macroprudential policy instrument (loan to value) is effective to control property loan. Then, simultaneously four independent variables significant effect on property loans and partially interest rates on consumer credit has no significant effect on property loans. Based on the coefficient of integration test result, the ability of independent variables in the model to explain the dependent variable changes is amounted to 62.68%.